University governance and academic work: the 'business model' and its impact on innovation and creativity - Shattock, M (Centre for Global Higher Education, University of Oxford, 2019)
Working Paper 48 is a transcript of the 2019 Burton R Clark lecture on higher education that Professor Shattock gave at the fourth annual conference of the Centre for Global Higher Education at the UCL Institute of Education in London on 3 April 2019.